2019
DOI: 10.1016/j.pmedr.2019.100860
|View full text |Cite
|
Sign up to set email alerts
|

Communication channels for air quality alerts in the United States

Abstract: Short-term exposure to air pollution can result in acute health effects, particularly for individuals with respiratory and cardiovascular disease. Air quality alert programs that notify the public about high air pollution days are critical for susceptible populations. We assessed how U.S. adults receive air quality alerts and whether it varies by demographic or health characteristics. We analyzed data from the summer 2014 wave of ConsumerStyles, a nationally representative survey of U.S. adults ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
3
5
0
Order By: Relevance
“…Air quality alerts on television reached the largest percentage of U.S. adults, reaching more than half of U.S. adults aware of air quality alerts. This is consistent with findings from 2014 ConsumerStyles data, although the proportion reporting this channel decreased from 76% to 58% ( Pennington et al, 2019 ). Declines in proportions receiving air quality alerts via television were especially pronounced for certain demographic groups, including non-Hispanic Black adults; among this group, the proportion receiving alerts via television decreased from 91% in 2014 ( Pennington et al, 2019 ) to 33% in 2020.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Air quality alerts on television reached the largest percentage of U.S. adults, reaching more than half of U.S. adults aware of air quality alerts. This is consistent with findings from 2014 ConsumerStyles data, although the proportion reporting this channel decreased from 76% to 58% ( Pennington et al, 2019 ). Declines in proportions receiving air quality alerts via television were especially pronounced for certain demographic groups, including non-Hispanic Black adults; among this group, the proportion receiving alerts via television decreased from 91% in 2014 ( Pennington et al, 2019 ) to 33% in 2020.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with findings from 2014 ConsumerStyles data, although the proportion reporting this channel decreased from 76% to 58% ( Pennington et al, 2019 ). Declines in proportions receiving air quality alerts via television were especially pronounced for certain demographic groups, including non-Hispanic Black adults; among this group, the proportion receiving alerts via television decreased from 91% in 2014 ( Pennington et al, 2019 ) to 33% in 2020. In contrast, we found that air quality alerts via an app on a mobile phone or device reached the second largest percentage of U.S. adults at 30% in 2020 compared with less than 6% in 2014 ( Pennington et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations